Innovation Activities and Integration through Vertical Acquisitions. (19th September 2019) - Frésard, Laurent; Hoberg, Gerard; Phillips, Gordon M
Abstract: We examine the determinants of vertical acquisitions using product text linked to product vocabulary from input-output tables. We find that the innovation stage is important in understanding vertical integration. R&D-intensive firms are less likely to become targets of vertical acquisitions. In contrast, firms with patented innovation are more likely to sell to vertically related buyers. Firms' R&D intensity is a more important deterrent to their vertical acquisitions when the provision of innovation incentives by potential acquirers is more difficult. The role of patents in fostering vertical acquisitions is more prevalent when potential buyers face a higher risk of holdup. ( JEL G32, G34, L22, L25, O34)